Studies in interactional linguistics - Selting, Margret; Couper-Kuhlen, Elizabeth (Studies in discourse and grammar, 2001)
Current interactional linguistic research appears to be crystallizing around systematic themes, which are all represented in this collection of papers. In the first section, where the relation between language and interaction is viewed from the perspective of language structure, several articles deal with the potential of a single structure for both turn and sequence construction, revealing a play-off between planned and occasioned syntax with potentially far-reaching consequences for language development. Other articles deal with lexical expressions as resources for the conduct of interaction.